2012
DOI: 10.1056/nejmra1108178
|View full text |Cite
|
Sign up to set email alerts
|

Membranoproliferative Glomerulonephritis — A New Look at an Old Entity

Abstract: M embranoproliferative glomerulonephritis (MPGN), also termed mesangiocapillary glomerulonephritis, is diagnosed on the basis of a glomerular-injury pattern that is common to a heterogeneous group of diseases. MPGN accounts for approximately 7 to 10% of all cases of biopsy-confirmed glomerulonephritis 1-4 and ranks as the third or fourth leading cause of end-stage renal disease among the primary glomerulonephritides. 2,5 Although some diseases associated with MPGN are well known, recent advances have identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
334
1
38

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 453 publications
(387 citation statements)
references
References 92 publications
5
334
1
38
Order By: Relevance
“…Light microscopy reveals a proliferative pattern of injury with evidence of mesangial, subendothelial, and, occasionally, subepithelial deposits on electron microscopy. 3,4 Clinically, the disease presents with hematuria, proteinuria, and low serum C3 levels. 2 The renal outcome of patients with C3GN is not as well established.…”
mentioning
confidence: 99%
“…Light microscopy reveals a proliferative pattern of injury with evidence of mesangial, subendothelial, and, occasionally, subepithelial deposits on electron microscopy. 3,4 Clinically, the disease presents with hematuria, proteinuria, and low serum C3 levels. 2 The renal outcome of patients with C3GN is not as well established.…”
mentioning
confidence: 99%
“…However, an infectious trigger may overwhelm this compensatory mechanism and lead to deposition of alternate complement components in the glomeruli, inciting various glomerular patterns of injury. 5 Other differential diagnoses of a C3 dominant IF profile include postinfectious GN and juvenile acute nonproliferative GN, discussed below. A small subset of cases of postinfectious GN (C3 dominant immunostaining profile, subepithelial humps on EM) have an atypical clinical course with persistent hypocomplementemia, hematuria, or proteinuria and progression to ESRD.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that dysregulation of the AP also results in C3GN. C3GN is characterized by glomerular C3 deposition and the presence of numerous deposits in the mesangium and capillary walls, including subepithelial deposits (21)(22)(23)(24). Thus, there is considerable overlap in the biopsy findings of patients with atypical postinfectious GN and those with C3GN (25).…”
Section: Discussion Of Questionmentioning
confidence: 99%